2022
DOI: 10.3390/polym14010196
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the Sustainability of Modified Pet-Based Multilayer Packaging Material with Enhanced Mechanical Recycling Potential and Processing

Abstract: Sustainability and recyclability are among the main driving forces in the plastics industry, since the pressure on crude oil resources and the environment is increasing. The aim of this research is to develop a sustainable thermoformable multilayer food packaging, based on co-polyesters, which is suitable for hot-fill applications and allows for recycling in a conventional waste stream. As a polymer material for the outer layer, we selected a modified polyethylene terephthalate (PETM), which is an amorphous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The findings of the study by Franz and Silva (2022), for example, point to physical and infrastructural difficulties. Trossaert et al (2022) showed that the lack of infrastructure is crucial for the success of the selective collection, while the study by Santos and Proença (2022) found that the lack of server experience, lack of information system, lack of infrastructure, and lack of technology prevents waste from being collected efficiently. The material causes correspond to the lack of infrastructure and materials and equipment necessary for the practice of reverse logistics; procedural causes concern the procedures of the population to do their part and share information and knowledge so that this practice becomes effective.…”
Section: Examples Of How Difficulties Happenmentioning
confidence: 99%
“…The findings of the study by Franz and Silva (2022), for example, point to physical and infrastructural difficulties. Trossaert et al (2022) showed that the lack of infrastructure is crucial for the success of the selective collection, while the study by Santos and Proença (2022) found that the lack of server experience, lack of information system, lack of infrastructure, and lack of technology prevents waste from being collected efficiently. The material causes correspond to the lack of infrastructure and materials and equipment necessary for the practice of reverse logistics; procedural causes concern the procedures of the population to do their part and share information and knowledge so that this practice becomes effective.…”
Section: Examples Of How Difficulties Happenmentioning
confidence: 99%
“…8 Polyethylene terephthalate (PET) is one of the most popular thermoplastic materials with good processing properties. 9 It is widely used in food and beverage preservation, electronics, medical devices, and other areas, [10][11][12] because of its good transparency, 13 corrosion resistance, 14 high thermal stability, 15 and low production cost. 16 In recent years, PET has also become an important flexible substrate material, 17 for flexible display panels.…”
Section: Introductionmentioning
confidence: 99%